2018
DOI: 10.1038/s41598-018-23510-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of IL-22BP in psoriasis

Abstract: IL-22 is a potent pro-inflammatory cytokine upregulated in psoriasis and in other inflammatory diseases. The function of IL-22 is regulated by the soluble scavenging receptor, IL-22 binding protein (IL-22BP or IL-22RA2). However, the role and regulation of IL-22BP itself in the pathogenesis of inflammatory disease remain unclear. We used the TLR7 agonist Imiquimod (IMQ) to induce a psoriasis-like skin disease in mice and found a strong downregulation of IL-22BP in the affected skin as well as in the lymph node… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 35 publications
(57 reference statements)
3
21
0
Order By: Relevance
“…Acanthosis was shown to be dependent on IL-22, because it affects the differentiation of keratinocytes (Boniface et al, 2005;Ma et al, 2008;Wolk et al, 2006). In line with that, we recently showed that the IL-22 inhibitor IL-22BP is down-regulated in skin of psoriasis patients compared with skin from healthy patients, enabling IL-22's function in the disease (Voglis et al, 2018). Here, we found that the cytokine IL-22 was not up-regulated in mice lacking an IL-17 response in KCs after IMQ treatment.…”
Section: Discussionsupporting
confidence: 59%
“…Acanthosis was shown to be dependent on IL-22, because it affects the differentiation of keratinocytes (Boniface et al, 2005;Ma et al, 2008;Wolk et al, 2006). In line with that, we recently showed that the IL-22 inhibitor IL-22BP is down-regulated in skin of psoriasis patients compared with skin from healthy patients, enabling IL-22's function in the disease (Voglis et al, 2018). Here, we found that the cytokine IL-22 was not up-regulated in mice lacking an IL-17 response in KCs after IMQ treatment.…”
Section: Discussionsupporting
confidence: 59%
“…They noted reduced expression of IL-22BP in mouse-model as well as in patients with psoriasis. They concluded that regulation of IL-22BP is a key step in the development of skin inflammation 47 . While the effect of IL-22BP is reversed in skin disease, its ability to regulate inflammation through action on IL-22 is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…There it blocks IL-22 signaling through the follicle-associated epithelium (FAE), allowing for reduced expression of mucin and antimicrobial peptides at a key Ag sampling locale. In DCs, IL-22BP is upregulated by retinoic acid (65) and downregulated by IL-18, inflammasome activation, or PGE 2 (66,67). This makes IL-22BP a scientifically interesting protein, as the majority of proteins studied in DC biology are upregulated, not downregulated, upon inflammation.…”
Section: How Does Il-22 Binding Protein Regulate Il-22 Biology?mentioning
confidence: 99%